Demographic and clinical profile of patients suffering prolonged severe hypoxia in COVID-19. Issue 9 (2nd September 2022) - Shah, Samir; Valiani, Dahnish; Balogun, Omotola; Zanoria, Martin Angelo; Jarrett, Simone; Hiedra, Raul; Patarroyo-Aponte, Gabriel; Azmaiparashvili, Zurab; Lo, Kevin Bryan; Eiger, Glenn
ABSTRACT: Background: Coronavirus disease 2019 (COVID-19) may result in rapid onset of hypoxemic respiratory failure. This study aimed to characterize the factors and outcomes associated with prolonged hypoxia in patients with COVID-19. Prolonged severe hypoxia (PSH) was defined as hypoxia requiring ≥6 L/min of oxygen by nasal cannula or equivalent for more than 10 days. Research design and methods: This study was designed as a single-center retrospective analysis. Multivariable logistic regression was utilized to assess factors associated with PSH. Results: The sample included 554 patients with 117 (21%) having PSH. Median length of stay of patients with PSH was significantly longer (median IQR: 18 days vs 6 days, p < 0.0001). Patients with PSH had significantly higher rates of venous thromboembolism (p < 0.0001) and major bleeding (p < 0.004). The presence of cirrhosis (OR 3.32, 95% CI [1.02 to 10.83]) and hypertension (OR 1.99, 95% CI [1.12 to 3.53]) were independently associated with PSH, while outpatient use of anti-platelet agents had an inverse association (OR 0.57, 95% CI [0.36 to 0.91]). Conclusion: PSH is associated with increased length of stay, morbidity, and mortality. Hypertension and liver cirrhosis were significantly associated with higher odds of PSH, while use of anti-platelet therapy had a protective effect.